IV Ogólnopolski Zlot Turystyczny. (Gdańsk : [s.n.], 1967)
Afisz inf. o zlocie 11-18 czerwca 1967 w ramach obchodów Dnia Stoczniowca.
Keywords: Stocznia Gdańska -- 1945-1970 -- druki ulotne; Turystyka -- Polska -- 1945-1970.